Protection system analysis using fault signatures - Mohd. Zin , Abdullah Asuhaimi (Penerbit UTM, 2007)
Power system fault is defined as an electrical fault, which involves the failure of primary electrical apparatus, resulting from the deviation of electrical parameters (i.e. voltage, current, frequency, power, etc.) from their normal operating values [1]. This situation requires the disconnection of the affected equipment by opening the relevant circuit breakers. Since the implementation of electricity deregulation, most of the power utilities have been operating their grid to its maximum capability limit due to commercial reasons. Therefore, consistent monitoring of the power system operation and performance have become mandatory to most of the countries throughout the whole world. However, system operators have to depend mainly on the relay indications, flags, fascia and Supervisory Control and Data Acquisition (SCADA) information flow.